Characterizing high and low accretion states in VY Scl CVs using ZTF and TESS data - Duffy, C.; Wu, Kinwah; Ramsay, G.; Wood, Matt A.; Mason, Paul A.; Hakala, Pasi; Steeghs, D. (Oxford University Press (OUP), 2025)
VY Scl binaries are a sub-class of cataclysmic variable (CV) which show extended low states, but do not show outbursts which are seen in other classes of CV. To better determine how often these systems spend in low states and to resolve the state transitions we have analysed Zwicky Transient Facility (ZTF) data on eight systems and Transiting Exoplanet Survey Satellite (TESS) data on six systems. Half of the sample spent most of the time in a high state; three show a broad range and one spends roughly half the time transitioning between high and low states. Using the ZTF data, we explore the colour variation as a function of brightness. In KR Aur, we identify a series of repeating outburst events whose brightness appears to increase over time. Using TESS data, we searched for periods other than the orbital. In LN UMa, we find evidence for a peak whose period varies between 3 and 6 d. We outline the current models which aim to explain the observed properties of VY Scl systems which includes disc irradiation and a white dwarf having a significant magnetic field.